Genetic cancer predisposition syndromes among older adults. Issue 7 (September 2020) - Chavarri-Guerra, Yanin; Slavin, Thomas P.; Longoria-Lozano, Ossian; Weitzel, Jeffrey N.
Abstract: Earlier age at onset is one characteristic of hereditary cancer syndromes, so most studies of genetic testing have focused on young patients with cancer. However, recent studies of multigene panel tests in unselected cancer populations have detected a considerable proportion of older patients with germline pathogenic variants (PVs) in cancer susceptibility genes. As the number of older patients with cancer continues to rise, clinicians should be aware of genetic/genomic cancer risk assessment (GCRA) criteria in both young and older adults. Identifying individuals with a germline PV in a cancer susceptibility gene may be important for precision therapy of current cancers and screening and prevention of new primary cancers, as well as cascade testing to identify high cancer risks for family members. Typically, hereditary predisposition germline genetic testing has been recommended for patients with early onset cancers and/or a family history of cancer. However, more recently international guidelines recommend testing for potential therapeutic intervention regardless of age for some tumors frequently seen in older patients, such as epithelial ovarian, pancreatic, and metastatic prostate and breast cancers. GCRA in older patients may present challenges including: clonal hematopoiesis (CH) confounding test interpretation, ethical aspects (autonomy, nonmaleficence, beneficence), patient health status, comorbidities, as well as lack of insurance coverage. These factors should be considered during genetic counseling and when considering cancer screening and risk reduction procedures. This manuscript reviews available data on common hereditary cancer syndromes in older patients and provides tools to help providers perform GCRA in this population.